An exciting synergistic effect: realizing large-sized MgH2 dehydrogenation at lowered temperatures by locally assembling a heterophase composite. (December 2019) - Zhang, Jiguang; Yao, Linglong; Liu, Wanqiang; Zhu, Yunfeng; Shi, Rui; Zhang, Yao; Ma, Zhongliang; Liu, Yana; Lin, Huaijun; Li, Liquan
Abstract: Fascinating hydrogen sorption properties of MgH2 are usually achieved by alloying, catalyzing, surface modification, and in most cases, nanosizing of either the grains or the particles because the bulk MgH2 is difficult to desorb H2 at mild conditions. Here an efficiently synergistic strategy to tune the desorption behavior of micro-sized MgH2 is proposed. Through a well-designed solid state hydriding combustion synthesis (HCS) process, Mg–Ni hydrides distribute uniformly throughout the whole particle, locally forming a multi-phase hydrides system. The whole hydrogen content is released at a lowered temperature characteristic of Mg2 NiH4 (210–240 °C). Desorption temperature of MgH2 in the multi-phase hydrides system is decreased by 173 °C and dehydrogenation activation energy is reduced by half compared with that of the simple mixture. A simultaneous desorption process of the multi-phase hydrides is firstly demonstrated by in situ X-ray diffraction, based on which a remarkable synergistic desorption mechanism is proposed, owing to the interfacial engineering and catalyzing effect of Mg2 Ni. Fresh insights into the cooperative effect between the distinct hydrides and other related complex systems are presented as well: when properly coupled, large bulk state hydrides (>20 μm) can also exhibit desirable practical behaviors, even in the absence of additional catalysts or modifying agents. Graphical abstract: A surprising synergetic effect derived from locally assembling multi phase hydrides, realizing desorption of large-sized bulk MgH2 at desirable temperatures. Image 1 Highlights: Mg2 NiH x uniformly dispersed into Mg80 Ni20 matrix with large-size. MgH2 desorption was greatly improved due to a remarkable synergistic effect. Desorption temperature of MgH2 was lowered by 173 °C and E a was reduced by half. A simultaneous desorption process was directly demonstrated by in situ XRD.